Records of Risso’s Dolphin, Grampus griseus, in Coastal Waters of Southern Argentina - Riccialdelli, Luciana; Torres, Monica Analia; Prosser Goodall, Rae Natalie; Dellabianca, Natalia Andrea; Pimper, Lida Elena; Reyes, Laura M.; Fernández Ajó, Alejandro; Bastida, Ricardo Oscar (Revista de biología marina y oceanografía)
We review the records of published and unpublished sightings and strandings for Risso’s dolphin (Grampus griseus) in subantarctic waters of the Southwestern South Atlantic Ocean. Based on 59 sighting (n = 521 individuals) and 33 stranding records (n = 88 individuals), we identified three main areas of Risso’s dolphin concentration in Patagonian waters, which have been observed mostly during the austral summer. We were unable to find published or unpublished reports of Risso’s dolphin in offshore or over deep-water areas in this region. Future studies covering other potential areas of the species’ distribution are important to improve the scarce information known for this dolphin in this area. Fil: Riccialdelli, Luciana. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Torres, Monica Analia. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Prosser Goodall, Rae Natalie. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Dellabianca, Natalia Andrea. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina Fil: Pimper, Lida Elena. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología, Genética y Evolución; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Reyes, Laura M. Universidad Nacional de la Patagonia; Argentina Fil: Fernández Ajó, Alejandro . Universidad Nacional de la Patagonia; Argentina Fil: Bastida, Ricardo Oscar. Universidad Nacional de Mar del Plata; Argentina. ...